Radiotherapy of Malignant Tumors: Photons or Protons? Part 1. Bragg Peak and the Brief Characteristics of a Proton Beam - G. A. Pan’shin; Z. S. Tsallagova; T. R. Izmailov (Вестник рентгенологии и радиологии)
The first paper of a series of three publications briefly presents the characteristics a proton beam, as well as the information of companies producing noncommercial techniques for photon and proton therapies. The following second and third parts will briefly consider the clinical and economic efficiency of proton versus photon radiotherapy in the treatment of cancer patients and prospects for its development in oncological practice.